Didactic Principles of Organizing Music Literacy Activities in Music Classes of General Education Schools - Tursunov Alimjon (PT ANTIS International Publisher, 2024)
In primary grades, children's singing in a soft tone ensures gentle and pleasant sounding of the voice. The use of hard ataka puts strain on children's voices. This interferes with the normal formation of singing skills. It has a negative effect on the development of voices. The article describes the didactic principles of organizing music literacy classes in music classes of general education schools.